Respuesta :

Answer:

a ) 7a

b ) 9x

c ) 4p

Step-by-step explanation:

a ) 2a + 5a

Take a common

= a ( 2 + 5 )

= a (7)

= 7a

b ) 12x - 3x

Take x common

= x ( 12 - 3 )

= x ( 9 )

= 9x

c ) 3p + 2p - p

Take p common

= p ( 3 + 2 - 1 )

= p ( 5 - 1 )

= p (4)

= 4p

[tex]\rule[225]{225}{2}[/tex]

Hope this helped!

~AH1807

Answer:

(A) is 7a

(B) is 9x

(C) is 4p

Step-by-step explanation:

(A) 2a+5a

(2+5)a

2+5=7

7a

(B) 12×-3×

(12-3)x

12-3=9

9x

(C) 3p+2p-p

(3+2-1)p

4p

Sorry if I did it wrong